Estimating vastus lateralis muscle volume from a single ultrasound image - Moritz Eggelbusch; Guido Weide; Michael Tieland; Renske N. Vergeer; Luuk Vos; Jantine van den Helder; Stephan van der Zwaard; Richard T. Jaspers; Peter J. M. Weijs; Rob C. I. Wüst (Scientific Reports)
Abstract The assessment of skeletal muscle volume is valuable for fundamental research and clinical practice, but remains limited in larger cohorts due to its time-consuming nature. Here, we developed a method to accurately estimate vastus lateralis (VL) muscle volume based on a single measurement of anatomical cross-sectional area (ACSA) or tissue thickness. Sixty-nine healthy participants (20–91 years) volunteered. In a subgroup (n = 34) we measured VL volume and ACSAs at 10% intervals along the muscle length to derive a VL muscle shape factor. We subsequently estimated VL volume by multiplying this muscle shape factor with muscle length and a single measure of ACSA at 50% muscle length (ACSAVL50%) or an estimated ACSAVL50% from a single ultrasound scan of tissue thickness in an independent cohort (n = 35). VL muscle shape factor was determined by integrating a fourth-order polynomial of muscle length and ACSA, and was dependent on muscle size. Estimating muscle volume had a high accuracy (R²=0.976, CCC = 0.987), low bias and error (< 8.5%) in both the main cohort and an independent validation group. Estimating muscle volume from stitching 2D images at 50% muscle length or estimating ACSA with a geometric model explained 91–95% of variance in measured volumes, with high accuracy and concordance correlation coefficients. VL muscle volume can be estimated by multiplying a muscle shape factor with muscle length and ACSAVL50% from a single ultrasound image. We present a novel, cost-effective, rapid, yet accurate assessment of VL muscle mass for (large-scale) studies and clinical practice.